Avoidance of similarity and brand attachment of Generation X in sportswear brand loyalty: The roles of self-congruity - Goi, Chai Lee; Yew , Fayrene Leh Chienga; Goi, Mei Teh
The purpose of this study is to examine the effects of avoidance of similarity, self-congruity, and brand attachment on Generation X’s sportswear brand loyalty. This study also examines whether self-congruity plays a role in the relationship between avoidance of similarity and brand attachment. A total of 368 valid data were used in this study and collected from Generation X participants. The hypotheses were tested using Structural Equation Modeling with the AMOS 22.0. The findings show that avoidance of similarity influences self-congruity, self-congruity influences brand attachment, avoidance of similarity influences brand attachment, and brand attachment directly influences brand loyalty. In addition, Self-congruity was found to partially mediate the relationship between avoidance of similarity and brand attachment. This study adds to the growing body of knowledge about avoidance of similarity and self-congruity as important drivers of brand attachment and brand loyalty. (Abstract by author)